Asymptotic Distribution of a Kind of Dirichlet Distribution (Communications in Mathematical Research, 2021)
The Dirichlet distribution that we are concerned with in this paper isvery special, in which all parameters are different from each other. We prove that theasymptotic distribution of this kind of Dirichlet distributions is a normal distributionby using the central limit theorem and Slutsky theorem.